2008
DOI: 10.1590/s1806-83242008000100016
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric assessment of the effects of 10% carbamide peroxide on enamel translucency

Abstract: Tooth shade results from the interaction between enamel color, enamel translucency and dentine color. A change in any of these parameters will change a tooth's color. The objective of this study was to evaluate the changes occurring in enamel translucency during a tooth whitening process. Fourteen human tooth enamel fragments, with a mean thickness of 0.96 mm ( 0.3 mm), were subjected to a bleaching agent (10% carbamide peroxide) 8 hours per day for 28 days. The enamel fragment translucency was measured by a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
(12 reference statements)
1
18
0
3
Order By: Relevance
“…Vieira 25 and Ma et al 14 reported that the bleaching procedure significantly changed the enamel translucency, making it more opaque. In the enamel-dentine system, along with the decrease in enamel translucency, more light was reflected within the enamel, leading to more light reflected to the human eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vieira 25 and Ma et al 14 reported that the bleaching procedure significantly changed the enamel translucency, making it more opaque. In the enamel-dentine system, along with the decrease in enamel translucency, more light was reflected within the enamel, leading to more light reflected to the human eye.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the object would seem lighter. 25 Enamel consisted of large amount of inorganic materials and very small amount of organic phase such as protein and water. 26 The decrease in translucency of enamel sample would be related to partial removal of mineralized tissues and organic matrix, which might be affected by the etching and oxidization of bleaching gels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The correlation of opacity and lightness of resin composites observed in this study correlates well with an in vitro study that demonstrated that whitening with 10% carbamide peroxide increases the opacity of enamel. 21 In this regard, resin composite materials designed for whitened teeth follow a similar pattern as natural enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Tagami et al (1989), mostraram que a permeabilidade da dentina coronal de incisivos bovinos é semelhante ao da dentina próxima à junção amelo-cementária dos dentes humanos. Schiavoni et al (2006) Vários pesquisadores utilizaram espectrofotômetros e colorímetros em suas pesquisas, (Frysh et al, 1995;Lenhard, 1996;O'Brien et al, 1997;Horn et al, 1998;Jones et al, 1999;Carvalho et al, 2002;Gallagher et al, 2002;Alves et al, 2006;Dietschi et al, 2006;Travassos et al, 2010;Wiegand et al, 2005;Caneppele, 2008;Vieira et al, 2008). A grande vantagem do uso de colorímetros ou espectrofotômetros em relação à visão humana é a objetividade da leitura, segundo Paul et al (2002), a determinação espectrofotométrica das cores é mais precisa e mais reprodutível em comparação com a avaliação visual (83,3% comparado a 26,6%).…”
Section: Discussionunclassified